2002
DOI: 10.1021/ja0268682
|View full text |Cite
|
Sign up to set email alerts
|

CO2 as a Separation Switch for Ionic Liquid/Organic Mixtures

Abstract: A novel technique to separate ionic liquids from organic compounds is introduced which uses carbon dioxide to induce the formation of an ionic liquid-rich phase and an organic-rich liquid phase in mixtures of methanol and 3-butyl-1-methyl-imidazolium hexafluorophosphate ([C4mim][PF6]). If the temperature is above the critical temperature of CO2 then the methanol-rich phase can become completely miscible with the CO2-rich phase, and this new phase is completely ionic liquid-free. Since CO2 is nonpolar, it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
241
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(246 citation statements)
references
References 20 publications
4
241
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32] scCO 2 has been used for extraction of products from RTILs. [33][34][35][36] The interaction between the solute and the solvent in the mixture can impart new properties which the individual components may not possess. 37 Although CO 2 is remarkably soluble in imidazolium based ionic liquids, 33,[38][39][40][41][42][43] ionic liquids such as [bmim][PF 6 ] do not dissolve much in CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32] scCO 2 has been used for extraction of products from RTILs. [33][34][35][36] The interaction between the solute and the solvent in the mixture can impart new properties which the individual components may not possess. 37 Although CO 2 is remarkably soluble in imidazolium based ionic liquids, 33,[38][39][40][41][42][43] ionic liquids such as [bmim][PF 6 ] do not dissolve much in CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-liquid extraction is also not desirable if the process aims to decrease environmental impact by decreasing the use of organic solvents. To avoid these problems, carbon dioxide, generally at high pressures, can be added to induce liquid-liquid phase separation in the mixture [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, development of new efficient solvents is the first step for the transformation and utilization of lignocellulose. As novel green solvents, ionic liquids (ILs) have many attractive properties, including negligible vapor pressure, non-flammability, thermal stability and recyclability, and have been used in organic synthesis, electrochemistry, catalysis, extraction and among others (Qian et al, 2005;Dupont et al, 2002;Scurto et al, 2002;Kubo et al, 2002). In 2002, Rogers and co-workers (Swatloski et al, 2002) found that some hydrophilic ILs are effective solvents for the dissolution of cellulose.…”
Section: Introductionmentioning
confidence: 99%